2013
DOI: 10.1177/1363461513487308
|View full text |Cite
|
Sign up to set email alerts
|

Internet suicide in Japan: A qualitative content analysis of a suicide bulletin board

Abstract: Netto shinju, or Internet group suicide, is a contemporary form of Japanese suicide where strangers connect on the Internet and make plans to commit suicide together. In the past decade, numerous incidents have occurred whereby young Japanese make contact on the Internet, exchange tips on suicide methods, and make plans to meet offline for group/individual suicide. A systematic qualitative content/thematic analysis of online communications posted on a popular Japanese suicide bulletin board yielded a textured,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…This was the largest category with 15 studies. Eleven studies examined the ways in which people used specifically designed online suicide forums, 14,21,28,[34][35][36][37][38][39][40] including those designed for people bereaved by suicide. 41 Two studies primarily focused on the ways in which moderators responded to messages posted in the forums, 42,43 and the final two studies examined both of these things.…”
Section: How Do People Use Social Media Sites For Suicide Prevention-mentioning
confidence: 99%
See 2 more Smart Citations
“…This was the largest category with 15 studies. Eleven studies examined the ways in which people used specifically designed online suicide forums, 14,21,28,[34][35][36][37][38][39][40] including those designed for people bereaved by suicide. 41 Two studies primarily focused on the ways in which moderators responded to messages posted in the forums, 42,43 and the final two studies examined both of these things.…”
Section: How Do People Use Social Media Sites For Suicide Prevention-mentioning
confidence: 99%
“…Overall, the findings appeared to be largely positive with a number of key advantages of using social media for this purpose highlighted. These included the ability of social media platforms to reach large numbers of otherwise hardto-engage people, 27 the visibility of expressions of suicidal ideation posted online, which can in turn allow others to intervene in, and potentially prevent, a suicide attempt, [28][29][30][31] and its acceptability in terms of providing an anonymous, accessible and nonjudgmental forum for sharing experiences with others and for both providing and receiving support; this was the case for both people who were suicidal themselves 38,40,46,48 and for those who had been bereaved by suicide. 41,51,52 Sites were generally governed by an ethical code of conduct and successfully moderated by trained volunteers who received professional supervision.…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, only 9.8% of incidents reported that they suffered from psychiatric disorders. However, previous studies found that 23% to 60% of suicide attempters had psychiatric disorders (Gunnell & Frankel, ; Ikunaga, Nath, & Skinner, ). This inconsistency might be due to a poor mental health literacy among Chinese people (Gong & Furnham, ; Rong et al, ; Wong & He, ), which leads to an underestimation of the prevalence of psychiatric disorders.…”
Section: Discussionmentioning
confidence: 93%
“…Demonstrations of curiosity about the game were found, as well as dissemination of information on the same. The scientific literature suggests that the media may have an important influence in suicide contagion, a phenomenon apparently caused by the improper communication on the theme 25 . Thus, information about suicide, if not carefully conveyed, can favor the spread of pro-suicide content 6 .…”
Section: Discussionmentioning
confidence: 99%